Twenty percent better with 20 micrograms? A qualitative study of psychedelic microdosing self-rapports and discussions on YouTube - Martin Andersson; Anette Kjellgren (BMC, 2019)
Abstract Background Psychedelic microdosing is the trending practice of using tiny repeated doses of psychedelic substances to facilitate a range of supposed benefits. With only a few published studies to date, the subject is still under-researched, and more knowledge is warranted. Social media and internet discussion forums have played a vital role in the growing visibility of the microdosing phenomenon, and the present study utilized YouTube contents to improve comprehension of the microdosing practice as well as the social interactions and discussions around microdosing. Methods Microdosing self-disclosure in YouTube videos and their following comments were qualitatively analyzed by inductive thematic analysis. Various software was utilized to enable gathering and sorting relevant data. Results Microdosing of psychedelic substances, primarily LSD and psilocybin, was used for therapeutic and enhancement purposes, and predominantly beneficial effects were reported. Many different applications and outcomes were discussed, and therapeutic effects for depression appeared especially noteworthy. Intentions for use were recognized as an influencing factor for the progression and outcomes of microdosing. The function of social interactions was mainly to discuss views on the microdosing phenomenon, strategies for optimal results, minimize risks, and share emotional support. Conclusions Potentially, microdosing could provide some of the same benefits (for certain conditions) as full-dose interventions with less risk of adverse reactions related to the sometimes intense experiences of higher doses. Microdosing may well also mean additional benefits, as well as risks, through the repeated exposure over extended periods.